Beyond the looking glass? 'Aidland' reconsidered. (September 2013) - Harrison, Elizabeth
This paper engages with an emerging genre in anthropology's engagement with international development – writing about 'Aidland' which focus attention on the lives, motivations and personalities of 'development professionals'. It suggests that there are two possible problems with the growing popularity of work on Aidland: first, that it rests on a reified and dated view of the worlds of aid and development; second, that an ethnographic focus on development professionals may serve to divert attention to the significance of both the politics and the material effects of development intervention and the relations of power within which they are embedded.